2021
DOI: 10.1111/jpi.12726
|View full text |Cite
|
Sign up to set email alerts
|

Night shift schedule causes circadian dysregulation of DNA repair genes and elevated DNA damage in humans

Abstract: jointly supervised the work (joint senior authorship).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 67 publications
(157 reference statements)
6
52
0
Order By: Relevance
“…Ideally, to properly assess a circadian oscillation (for instance, in activity, melatonin oscillation, or mRNA oscillation), a researcher conducts serial measurements in 2–4 h increments across several days, and then tests for oscillations in these time-series data. Indeed, this technique is quite feasible with serial sampling of human blood from volunteers, and has revealed that night shift work may be a risk factor for DNA damage that can lead to cancer [ 170 , 171 ]. However, serial sampling of most solid tumors is impossible due to ethical and practical considerations.…”
Section: Clinical Applications: Myc Inhibition and Measurement Of The Molecular Clock In Patientsmentioning
confidence: 99%
“…Ideally, to properly assess a circadian oscillation (for instance, in activity, melatonin oscillation, or mRNA oscillation), a researcher conducts serial measurements in 2–4 h increments across several days, and then tests for oscillations in these time-series data. Indeed, this technique is quite feasible with serial sampling of human blood from volunteers, and has revealed that night shift work may be a risk factor for DNA damage that can lead to cancer [ 170 , 171 ]. However, serial sampling of most solid tumors is impossible due to ethical and practical considerations.…”
Section: Clinical Applications: Myc Inhibition and Measurement Of The Molecular Clock In Patientsmentioning
confidence: 99%
“…However, inflammation can also induce other metabolic, immunosuppressive, and epigenetic changes that are also key to cancer progression. Other food or lifestyle carcinogens identified by IARC such as red meat, wood dust, hot beverages, night shift work, oral contraceptives, and post-menopausal estrogen therapy appear to cause cancer through inflammation, irritation, disrupted circadian rhythm, or chemical activation of cell growth pathways [81][82][83].…”
Section: Cancer As An Environmental Disease (The Exposome View)mentioning
confidence: 99%
“…Moreover, environmental or physiological perturbation of circadian rhythms such as shift work, abnormal sleep timing, irregular psychosociological stresses, and illness, can cause interindividual variability in both cancer growth and the response to cancer therapy (Y. Lee et al, 2019a;Walker et al, 2020a;Koritala et al, 2021). Circadian disruption may also be related to the chronic sleep loss and depression suffered by many cancer patients following diagnosis and treatment (Innominato et al, 2014;Telias and Wilcox, 2019).…”
Section: Circadian Regulation Of the Tumor Cell Cycle Can Affectmentioning
confidence: 99%